POLEMIK AL-SAHABAH KULLUHUM ‘UDUL DALAM PERIWAYATAN HADIS - Zikri Darussamin (UIN Siber Syekh Nurjati Cirebon, 2023)
This article aims to investigate the rules of al-sahabah kulluhum 'udl. The rule of al-sahabah kulluhum 'udl is a concept that considers all of the Prophet's companions to be fair. According to Sunni scholars, a shahabah or companion is a